#TITLE_ALTERNATIVE# - SHOLIHUL FATHONI (NIM : 23315005), HAPPY
Boilers are common industrial equipment that heat water to produce steam. The steam can be used for several purposes such as (1)for Steam Turbine Generator; and (2)Heating Process. In a boiler, a steam drum has a function to contain water that will be heated and then generate steam. The steam requirement for the process can be vary, so the right control methods are needed to maintain the water level in the steam drum appropriately. If the water is too low, the overheating can be detrimental to the steam drum, on the contrary, the higher of the water level compared to the set point can lead to the ineffective steam production. The problem in this research is how to control the steam drum water level appropriately, despite the incoming disturbances. Disturbance to water level occur due to the variation of the outlet valve opening to adjust the steam needed in the process. The usual method to control the level in the steam drum is PID. The PID method is one of the oldest methods that is still effective to control the water level. The purpose of this study is to classify the inlet valve opening based on the training data to minimize the effect of disturbances on a steam drum boiler by using Support Vector Machine (SVM) method. By minimizing the influence of the disturbances, the water level can be controlled based on a set point. Step to use SVM method are: (1) Obtain the training data set; (2)Training based on the obtained data; (3)Testing the generated model; (4)Conducting test on measured data; (5)comparing the results of the measured data with the output data of SVM. The classification percentage of Manipulated Variable (MV) using SVM method has shown agreeable error when comparing with the measurement results. The detail can be described as follows: (1)Training data 1 with the switch off and on condition of the inlet pump has Root Mean Square Error (RMSE) of 3.3%; (2)Training Data 2 has a RMSE of 1.6% while the pass area of the outlet valve as disturbance were changed between 25%-100% with 5% step; (3)Training data 3 has RMSE about 2% while the pass area of the outlet valve as disturbance were changed between 30%-100% with 10% step; (4)Training data 4 has RMSE of 2.3% while the pass area of the outlet valve as disturbance were changed between 100%-30% with 10% step; (5)Training data 5 has RMSE of 2.7% while changing the set point. It can be concluded that by using the SVM method, the water level in the steam drum boiler can be controlled properly because the well classification of the inlet valve opening. The RMSE values that occurred in the five experimental categories were 3.3%; 1.6%; 2%; 2.3%; and 3.5%. In other words, this SVM method can be an alternative controller to maintain the level of steam drum in addition to PID.